Woody De Othello - maybe tomorrow - Biswas, Allie; Shechet, Arlene 1951- (Karma Books, 2023)
The San Francisco based artist Woody De Othello (born 1991) finds inspiration for his paintings and ceramics by adapting a position of porousness to the things around him. Through his adroit interventions, everyday artifacts of the domestic tables, chairs, television remotes, telephone receivers, lamps and air purifiers are anthropomorphized in glazed ceramic, bronze, wood and glass. The result is often tubular, drooping and coated in vibrant reds, purples and magnetic blacks, imbued with the subterranean futurity of jazz. Fittingly, this catalog, published following the eponymous solo exhibition in New York, is titled after jazz musician Grant Green's 1971 tune. The new body of ceramic works in Maybe Tomorrow brim with spiritual charge; the domestic objects are treated as repositories of psychic significance. The catalog explores this thematic wellspring, along with other topics, in an essay by Jason R. Young, as well as in two conversations with the artist. Exhibition: Karma, New York, USA (24.09-05.11.2022)
Keywords: Othello, Woody De -- 1991-; Keramik; Ausstellungskatalog -- Karma -- 24.09.2022-05.11.2022 -- New York, NY.; Bildband